CHARACTER EDUCATION FOR WOMEN: Case Study of Madrasah Mu’allimaat Muhammadiyah Yogyakarta - Syahdara Annisa Ma’ruf (Universitas Muhammadiyah Surakarta, 2019)
The present study aims at determining the character education implemented in the extracurricular and extracurricular activities, strategy, and expectations for the alumni of Madrasah Mu’allimaat Muhammadiyah Yogyakarta with their contributions to family, society and national life. It is a qualitative study by using descriptive method. The findings of this study reveal that the realization of character education in Madrasah Mu’allimaat Muhammadiyah Yogyakarta employs a holistic approach model. All members of this institution, namely director, boarding school managers, religious teachers, employees, general teachers, students, and dormitory staff should be involved and responsible for the accomplishment of character education. Rules are devised to uphold character values through self-motivation that can be used to inculcate the character values in students. They should entail reinforcement, reward, and incentive. Madrasah Mu’allimaat Muhammadiyah Yogyakarta strives to prepare its graduates with the “3D concept” in which the alumni will be “noticed”, “recognized”, and “needed” by the society.